Effect of autologous amniotic membrane and fluid on wound healing and complications of cesarean section: Study protocol of a factorial randomized controlled trial - Kasra Jafari; Marzieh Vahid-Dastjerdi; SeyedAhmad SeyedAlinaghi; Amene Abiri (PLoS ONE, 2025)
Background Cesarean section rates have risen globally. While a cesarean section offers benefits, it is associated with complications like infection, fluid collection, and wound dehiscence. The psychological impact of cesarean section scars can also affect women’s quality of life. Amniotic membrane and fluid have shown promise in enhancing wound healing due to their rich content of growth factors and nonimmunogenic properties. This study aims to assess the effects of autologous amniotic membrane and amniotic fluid on wound healing, surgical site infection, pain, and complications following cesarean section. Materials and methods This controlled, randomized, double-blind (participants and the physician assessing outcomes are blinded), 2 × 2 factorial trial with a sample size of 228 is being conducted at Arash Women’s Hospital, Tehran, Iran. It involves four groups: amniotic membrane dressing, amniotic fluid spray, a combination of both, and one group receiving standard of care, assessing the effects of autologous amniotic membrane and amniotic fluid on cesarean section wound healing, infection, pain, and complications. Primary outcome (wound healing) would be measured by the Patient and Observer Scar Assessment Scale. Secondary outcomes are surgical site infection, pain via the Visual Analog Scale, surgical wound dehiscence, seroma, hematoma, and bleeding. Results will be analyzed using two-way ANOVA and logistic regression. Discussion This research protocol is the first to examine autologous amniotic membrane and amniotic fluid effects on cesarean section scar healing and complications. If effective, amniotic membrane and amniotic fluid could enhance CS scar aesthetics and reduce complications without extra cost. Trial registration This trial was registered at the Iranian Registry of Clinical Trials (Registration number: IRCT20220408054454N1 , Registration date: 2024-07-15 ).